P295 Prevalence of STIs among nepalese women population. (14th July 2019) - Upreti, Prasanna
Abstract : Background: Sexually transmitted infections (STIs) cause considerable morbidity worldwide, especially among women of reproductive age. Data on STI prevalence in Nepal are limited, and prevention and control programs have focused primarily on HIV infection. According to national reports, the estimated prevalence of HIV infection was 0.2 - 0.3% in 2013. In high-risk populations, however, there has been observed a concentrated HIV epidemic with an infection prevalence of 1.7 - 18.3%. So far, data on other STIs from Nepal are mostly derived from hospital or health-camp records or from high-risk populations. Methods: A population-based study of non-pregnant women with age 15 years and above, who were married or had a history of marriage in the past, residing in rural communities in Nepal. Data on sociodemographic characteristics, reproductive history, and genitourinary symptoms were collected, and a gynecological examination was also conducted. Cervical samples were analyzed by real-time PCR for Neisseria gonorrhoeae, Chlamydia trachomatis, and Trichomonas vaginalis and HPV, and a serum sample was analyzed for syphilis, hepatitis B virus (HBV) and HIV infection by serology. Results: Of 3570 eligible women, 73% participated. Trichomoniasis, Chlamydia trachomatis infection, HPV and HBV infection, and syphilis were detected in 7.2%, 1.2%, 11.4%, 1.7%, and 1.5% of the women. None had gonorrhea or HIV infection. Of those with genitourinary symptoms, 9.4% had a curable STI. Vaginal discharge classified as abnormal by gynecological examination, but not self-reported discharge, was significantly associated with laboratory diagnosis of a curable STI. Risk factors for trichomoniasis were reproductive age and high cast/ethnicity. Due to low prevalence, risk factors for other STIs could not be accurately determined. Conclusion: We observed a high prevalence of HPV infection followed by trichomoniasis, while other STIs were rare among women in rural Nepal. There was no association between genitourinary symptoms and laboratory-confirmed STIs. Disclosure: No significant relationships.